Lastništvo stanovanj v Sloveniji - Sendi, Richard (Urbani izziv, 2017)
Recent studies generally show growing levels of homeownership across Europe. However, a comparison of statistical data shows a stark difference in the extent of homeownership between western Europe versus central and eastern Europe. Whereas the development and growth of homeownership in western Europe has been extensively discussed in the literature and various theories have been advanced, its strong dominance in central and eastern Europe has been barely examined. Due to the lack of thorough discourse on this topic, there thus continues to be a void in the literature, which is manifested in the absence of a sound explanation for the comparatively much higher expansion of homeownership in post-communist central and eastern Europe. This article contributes to filling this gap. The central argument is that theories that were developed to explain the growth of homeownership in western Europe%(economies with a capitalist tradition) might not necessarily apply to situations in central and eastern Europe%(with previous communist centrally planned economies). Focusing on the case of Slovenia, the discussion is orientated towards developing an alternative theory that may be more relevant in explaining and understanding the growing preference for homeownership in the country.
Keywords: hiše; lastništvo; Slovenia; Slovenija; stanovanja; stanovanjska politika